Manajemen Sekolah: Meningkatkan Efektivitas dan Efisiensi Pendidikan SDN 12 Banda Aceh - Mutmainnah Mutmainnah; Novi lidya isdarianti (Journal on Education, 2024)
This article discusses school management at SD Negeri 12 Banda Aceh as an effort to increase the effectiveness and efficiency of education. Observation methods include direct observation, interviews with relevant stakeholders, and analysis of documents related to school management, with a focus on management of facilities and infrastructure, curriculum, students, human resources, and school budget. Observation results show that school management at SD Negeri 12 Banda Aceh includes resource management, school policies, interactions between staff and students, as well as implementation of educational programs. The main aim of this observation is to understand in depth the management practices implemented in daily activities at the school in order to achieve the stated educational goals. The observation process includes observing various situations and interactions at school, both inside and outside the classroom, including school leadership, policy implementation, and interactions between school stakeholders. The results of observations are recorded in the form of field notes, audio/video, or images and then analyzed to identify patterns, themes, and important findings related to research objectives. School management observations are often used in conjunction with other data collection methods, such as interviews or document analysis, to provide a comprehensive understanding of management practices in schools. From the results of observations at SD Negeri 12 Banda Aceh, important findings were found regarding school management including management of facilities and infrastructure, teacher and student recruitment processes, and budget management. Recommendations for improvement are provided to increase the effectiveness and efficiency of education at the school. Evaluations and improvements continue to be carried out in order to achieve better educational standards, with the hope that the positive contribution from these observations can bring about significant changes in the quality of education at SD Negeri 12 Banda Aceh and become a reference for other educational institutions.